Open Science for Accelerating the Sustainable Development Goals: Status and Prospects in Asia and the Pacific - Camkin, Jeff; Neto, Susana; Bhattarai, Basundhara; Ojha, Hemant; Khan, Shahbaz; Sugiura, Ai; Lin, Jiaying; Nurritasari, Fitrie Atviana; Karanja, Joseph Muiruri (Frontiers in Political Science, 2022)
Achieving the United Nations Sustainable Development Goals is increasingly challenging due to widening inequality in access to scientific and technological knowledge and resources. With science remaining too discipline based, and policymakers too often science averse, there is a need for greater understanding of the opportunities and challenges of open science for science practitioners, policy makers and communities. Acknowledging that open science can be a powerful tool to reduce inequalities, UNESCO has been supporting the shift to open science. Following global multistakeholder consultation, the UNESCO Recommendation on Open Science was adopted in November 2021, establishing a universal definition, common standards and shared set of values and principles. In 2021, the UNESCO Regional Science Bureau for Asia and the Pacific partnered with the Institute for Study and Development Worldwide on local and national mapping to identify implementation strategies and mechanisms already in place to enable open science in Asia and the Pacific, and to identify what more is needed. Focused on Malaysia, Republic of Korea, Pakistan, Samoa and Uzbekistan, the study showed that while there are many examples of good practice in aspects of open science, none of the focus countries currently has in place all the policies, infrastructure, awareness and capacity building needed. Typically, clear policies on open science have not yet been articulated and funding mechanisms not yet established. Trust is a key pre-requisite for open science. Current inequities in access to open science infrastructure will need to be addressed or implementation may be unbalanced, exacerbating existing inequities at national, regional, and global scales. There are many opportunities to learn from existing efforts toward open science, but there will be no generic model; each country will need to design an open science model and implementation pathway suited to its context. A predominant message from this research was that the convening power of UNESCO should continue to be harnessed to engage countries on open science implementation. Further, those committed to open science will need to work hard, with UNESCO, to democratize science and encourage an ethos of “policy for science, science for policy - science for society and society for science”.